Analytical Assessment of Poultry Feed Production in Animal Husbandry (International Journal of Engineering and Computer Science, 2019)
The cost of Poultry feed represents over 70% of the total cost of poultry production in Nigeria and elsewhere in the globe. This has however not reduced interest shown in poultry agriculture in recent times as contributions from this sector have impacted positively on national economy.  Efficient formulation regime devoid of inefficient feed production practices is required for poultry husbandry sustainability. This paper aims to make an analytical assessment of poultry feed production in animal husbandry in Nigeria with a view to finding out how each of the examined methods has helped the growth of this all important industry. The objective is to recommend a software that can solve mixing or blending problem facing a poultry farmer while using locally available feed ingredients at his disposal. It is hoped that the choice method shall minimize cost of producing a particular feed without compromising its adequacy as a balanced diet, which will in turn reduce the cost of overall production of poultry birds. The methodology employed in this paper is Structured System Analysis and Design Methodology (SSADM). A top down Software design approach was followed. The expected result included affordable and acceptable poultry feed production modelling system that grants a high return on investment (ROI) to the poultry farmer. The research work shall be useful to the present and upcoming poultry farmers, who would want to take poultry agriculture as an entrepreneur. It would also encourage further research in this area of study.